The Effect of Nutrition Education Using Pocketbook Media on Iron and Protein Intake - Syarief, Osman; Rezky Dwiayu, Anisya; Mulyo, Gurid P. E.; Nur Fauziyah, Roro; Aminah, Mimin; Surmita, Surmita; Cahyaningsih, Henny (Open Access Macedonian Journal of Medical Sciences, 2021)
The provision of nutrition education for teenage girls is an alternative to increase protein and iron intake to prevent anemia. This study aims to determine nutrition education's effect using pocketbook media on protein and iron intake in teenage girls. The research design used was quasi-experimental with a control group pre and post-test design. Sampling was done by the purposive sampling method—statistical analysis using Paired Samples T-test, Wilcoxon, Independent Samples T-test, and Mann Whitney. This study indicates an influence of nutrition education using pocketbook media on protein intake (p = 0.000) and iron (p = 0.000) in the treatment group. There is no effect of nutrition education using PowerPoint on protein intake (p = 0.326) and substances iron (p = 0.52) in the control group. Statistically, there was a significant difference between protein intake (p = 0.000) and iron (p = 0.001) of the treatment and control groups. It is recommended that UKS and students work together to conduct nutrition education routinely so that the nutrition information delivered can be given to all students in the school to prevent nutritional anemia.